2003
DOI: 10.1038/sj.ijir.3901056
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with erectile dysfunction in male kidney transplant recipients

Abstract: A transversal study was carried out in order to evaluate the prevalence of erectile dysfunction (ED) in adult kidney transplant patients of our region (N ¼ 243), and to investigate the sociodemographic, analytic, and clinical factors associated with it. To evaluate ED, the Spanish five items version of the International Index of Erectile Function (IIEF-5) was employed. Sociodemographic, analytic, and clinical data, including 12 cardiovascular risk factors, were also collected. A total of 199 patients (82%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 20 publications
3
31
1
1
Order By: Relevance
“…5,11 This was not confirmed in our study. Other studies have also not documented the relation between duration of dialysis and ED.…”
Section: Erectile Dysfunction In Renal Transplant Recipientscontrasting
confidence: 56%
See 2 more Smart Citations
“…5,11 This was not confirmed in our study. Other studies have also not documented the relation between duration of dialysis and ED.…”
Section: Erectile Dysfunction In Renal Transplant Recipientscontrasting
confidence: 56%
“…The importance of increased age on the prevalence of ED in the renal transplant population has been verified in several studies. 5,10,11 In Malavaud and colleagues' study of 271 post renal transplant patients, the average age of patients with ED was 49.2 years old, compared with 44.5 years old for patients without ED. 5 The mean age of patients with ED after renal transplant in another study was 43.6 years old, compared with 34.9 years old in patients without ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Cerqueira et al and Miyata et al found a significant association between ED and diabetes with respective p-values of 0.05 and 0.04 (18,24). Thus, according to many writers, these pathologies are involved in the development of ED (7,20,25). Chronic liver disease related to hepatitis virus B or C and heart failure, which are described as potentiating factors of sexual dysfunction in patients on dialysis (9,19,20), were objectified in one-third of our patients with 95.5% of them presenting ED.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 50% of patients with end-stage renal disease and 75% of patients on chronic dialysis therapy are affected 12 In a cross-sectional study of 323 kidney transplant patients, 13 the authors found that factors significantly and negatively related to ED in these patients were age, time on dialysis and iterative transplants. In a previous study, 14 we have reported the prevalence of ED found in kidney transplant patients of our region (54.9%) and the factors associated to this high prevalence (greater age, longer time on dialysis prior to transplantation and presence of peripheric arteriopathy). However, we did not find any published study focused on the association between ED and HRQoL in kidney transplant patients.…”
mentioning
confidence: 99%